Assessing and ranking HALMAS parks in Malaysia: An application of importance-performance analysis and AHP - Islam, Rafikul; El Madkouri, Fatima (Emerald Group Publishing Ltd., 2018)
Purpose This paper aims to measure the level of importance and satisfaction on a number of items in the day-to-day running of the halal parks in Malaysia and to rank a selected halal parks on the basis of a number of performance criteria.